Impact of Sector Level Variables on Political Scenarios in Pakistan - Ramakrishnan, Suresh; Nabi, Agha Amad; Daud, Zulkarnain; Anuar, Melati Ahmad (International Journal of Economics and Financial Issues, 2016)
Pakistan has a long history of involvement in politics. Since independence in 1947 the country has experienced four coups that directly rule of the country over time. Most recently in 1999 the armed forces took over the democratic government. Accumulated political and economic crunches that shaped the situation in which the armed involvement would get extensive public support. In the recent period from 2008 onwards democrats are ruling the country and there has been an extensive criticism of financial administration of the preceding government but no positive amendment has been seen in financial plans in this period either. This paper wants to compare the performance of sectors in different political regimes. Sector level variables are Munificence, Dynamism, Herfindahl-Hirschman Index (HH Index) and Uniqueness has been used to check the impact of sectors in different political regimes. Data has been segregated between two eras (i.e., 2004 to 2008 dictatorship periods and 2009-2013 democratic period). Paired sample t- test will be used to check the impact of sectors nature in two different regimes. Keyword: Sector level variables, Political periods, Democratic, Dictatorship. JEL Classification: G3